COVER BODY SIZE DIFFERENCES BETWEEN HEALTHY AND SICK MEN AND WOMEN WITH PYOGENIC SKIN INFECTIONS - Krivko, Yu.Ya.; Chaplyk-Chyzho, I.O. (World of Medicine and Biology, 2015)
In healthy man and women and patients with pyoderma differences in cover body size were determined. In women, suffering from pyoderma, significantly higher values of circumference of the shoulder in tense and rest, arm and leg in the upper and lower thirds, girth of neck, waist, hips, thighs, chest on inhalation, exhalation and at rest were defined as compared with healty women. In male patients with pyoderma only the value of hip circumference has a pronounced tendency to higher values, as compared with healthy men.